Large plants enhance aboveground biomass in arid natural forest and plantation along differential abiotic and biotic conditions - Yang, Bai-Yu; Ali, Arshad; Xu, Ming-Shan; Guan, Min-Sha; Li, Yan; Zhang, Xue-Ni; He, Xue-Min; Yang, Xiao-Dong (Frontiers in Plant Science, 2022)
Big-sized trees, species diversity and stand density affect aboveground biomass in natural tropical and temperate forests, however, these relationships are unclear in arid natural forest and plantation. Here, we hypothesized that large plants (a latent variable of tall-stature and big-crown; which indicated the effect of big-sized trees on ecosystem function and structure) enhance aboveground biomass in both arid natural forest and plantation along the gradients of climate water availability and soil fertility. To prove it, we used structural equation modeling (SEM) to test the influences of large plants located in 20% of the sequence formed by individual size (a synthetical value calculated from tree height and crown) on aboveground biomass in natural forest and plantation while considering for the direct and indirect influences of species diversity as well as climatic and soil conditions, using data from 73 natural forest and 30 plantation plots in northwest arid region of China. The results showed that large plants, species diversity and stand density increased aboveground biomass. Soil fertility declined aboveground biomass in natural forest, whereas increased biomass in plantation. Although climatic water availability had no direct impact on aboveground biomass in both forests, it indirectly controlled the change of aboveground biomass via species diversity, stand density and large plants. Stand density negatively affect large plants in both natural forest and plantation. Species diversity positively affect large plants in plantation but not in natural forest. Large plants increased slightly with increasing of climatic water availability in natural forest but decreased in plantation, whereas soil fertility inhibited large plants in plantation only. This study highlights the extended generality of the big-sized trees hypothesis, scaling theory and global importance of big-sized trees in arid natural forest and plantation.